Knowledge & Attitude among Parents of Children with Bronchial Asthma whom Attending Iraq Pediatric Hospital - Al Quraini , Abrar Naser Hasan Ali (South Asian Journal of Social Sciences and Humanities, 2024)
Background: Asthma is a prevalent chronic condition in pediatric populations. The rising incidence, morbidity, and mortality rates associated with asthma have heightened public health concerns. Pediatric asthma imposes a substantial burden on affected children, their families, and the broader community. Effective asthma management encompasses regular monitoring, symptom control, and the prevention of exacerbations. Objectives: The study aimed to document the knowledge, attitudes of parents of children with asthma and to identify the factors associated with parent knowledge and attitude. Method: A study was conducted involving 205 parents of children under five years old with asthma, who attended the Karbala Pediatric Hospital between February 15 and May 15, 2023. A specially designed questionnaire was utilized, comprising three sections: the first section addressed socio demographic information of both children and parents, the second section evaluated the parents’ knowledge, and the third section assessed the parents’ attitudes. Responses were scored with one point for correct answers and zero points for incorrect or "I don’t know" answers. Statistical analyses, including the Student’s T-test, ANOVA, and linear regression, were employed to identify factors associated with parental knowledge. Results: The results indicated that the majority of participants were mothers, with a mean age of 29 years, and the majority of asthmatic children were male (69.3%), with a mean age of 34.4 months. It was found that 48.8% of participants had a poor knowledge score, while 61% had a poor attitude score. Key factors influencing knowledge scores included the family’s place of residence, the child’s birth order, the duration of the disease, the age at disease onset, the participant’s age, and the mother’s educational level. Conclusion: Overall, the parents demonstrated limited knowledge and unfavorable attitudes regarding childhood asthma. Enhancing their understanding and attitudes could potentially lead to improved management practices among parents of children with asthma.